2013
DOI: 10.1021/jp4008152
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody Self-Association, Cluster Formation, and Rheology at High Concentrations

Abstract: The rheological properties of macromolecular and colloidal suspensions are dependent on the thermodynamic and kinetic parameters that define viscous flow, and remain an active field of study with broad implications in cellular biophysics, soft-matter theory, and biopharmaceutical technology. Here we use static light scattering, small-angle X-ray scattering, and viscosity measurements as a function of protein concentration to semiquantitatively correlate the oligomeric state of an IgG1 antibody (mAb1) with its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
209
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(229 citation statements)
references
References 58 publications
19
209
1
Order By: Relevance
“…10 For example, Pathak et al demonstrated that the presence of reversibly associated clusters at high protein concentrations contributed to an increase in solution viscosity. 52 Similar trends in viscosity in response to changes in solution conditions that we describe here for mAb-C have been reported for other IgG1 mAbs, where the extent of viscosity increased in a concentration-dependent manner with increasing ionic strength 11,18,30,53,54 and solution pH, 11,55 related to elevated levels of protein RSA due to charge shielding effects. [56][57][58] The isoelectric point (pI) range of mAb-C is basic (pI»9.1-9.4), 45 and therefore, the overall surface charge of mAb-C is expected to be positive at neutral pH.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…10 For example, Pathak et al demonstrated that the presence of reversibly associated clusters at high protein concentrations contributed to an increase in solution viscosity. 52 Similar trends in viscosity in response to changes in solution conditions that we describe here for mAb-C have been reported for other IgG1 mAbs, where the extent of viscosity increased in a concentration-dependent manner with increasing ionic strength 11,18,30,53,54 and solution pH, 11,55 related to elevated levels of protein RSA due to charge shielding effects. [56][57][58] The isoelectric point (pI) range of mAb-C is basic (pI»9.1-9.4), 45 and therefore, the overall surface charge of mAb-C is expected to be positive at neutral pH.…”
Section: Discussionsupporting
confidence: 82%
“…can either increase or decrease the extent of RSA of mAbs, depending on the distinct nature of the non-covalent interactions for an individual mAb formulated under specific conditions. 18,19 A variety of analytical tools have been used to characterize the RSA of proteins, and related effects on solution properties, including dynamic light scattering (DLS), 21 composition-gradient multi-angle static light scattering, 20,21 isothermal titration calorimetry, 15 surface plasmon resonance, 22 proton magnetic relaxation dispersion, 23 nuclear magnetic resonance, 24 fluorescence resonance energy transfer, 25 mass spectrometry (MS), 26 self-interaction nanoparticle spectroscopy, 27 size-exclusion chromatography, 28 analytical ultracentrifugation, 29 small angle X-ray scattering, 30 and atomic force microscopy. 31 Most of these measurements provide reliable data only at low-to-moderate protein concentrations (»1-20 mg/mL).…”
Section: Introductionmentioning
confidence: 99%
“…In qualitative agreement with the findings of Binabaji and coworkers, Lilyestrom et al also noted that clusters consisting of as many as nine antibody molecules are present in an antibody solution at 175 mg per mL that has viscosity of approximately 450 cP. 41 Additionally, recent computer simulations also suggested that higher-order antibody networks can form in certain antibody solutions at concentrations above 100 mg per mL. 42 The higher order networks and structures within liquids can be probed by oscillatory rheometry experiments using a time variant stress.…”
Section: Theoretical Foundations and Experimentally Measurable Quantisupporting
confidence: 83%
“…An elongated dimer was assigned a probable solution in SAXS measurements of dilute mAb solutions. 30 Furthermore, molecular dynamics simulation detected an elongated dimer as lowest energy minimum under certain conditions. 31 Elongated mAb dimers that are similar to those described here and were generated by process and light stress have been analyzed previously using TEM analysis.…”
Section: Discussionmentioning
confidence: 97%